Barriers to Basic School Teachers' Implementation of Formative Assessment in the Cape Coast Metropolis of Ghana - Asare Eric; Afriyie Elizabeth (De Gruyter, 2023)
Despite the identified benefits of formative assessment to teaching and learning, its implementation in the classroom remains a significant challenge to teachers. This has widened the gap between the theory and practice of formative assessment in the classroom to enhance students' learning. This study investigated the potential resource-related factors that affect basic teachers' adoption of formative assessment in their classrooms. A descriptive survey design with a multistage sampling procedure was employed to select 300 teachers from the six circuits in the Cape Coast Metropolis of Ghana. Data gathered were analyzed using descriptive (mean values, SD) and inferential statistics (two-way ANOVA). Time, workload, overcrowded curriculum, class size, and the number of lessons were reported as barriers to the effective implementation of formative assessment. Findings also revealed no statistically significant interaction effect of gender and grade level on the resource-related barriers. Moreover, grade level and gender had no statistically significant main effects with respect to the resource-related barriers. Recommendations and implications for policy, practice, and future research are discussed.